2017
DOI: 10.1002/2016wr019817
|View full text |Cite
|
Sign up to set email alerts
|

Little impact of the Three Gorges Dam on recent decadal lake decline across China's Yangtze Plain

Abstract: The ubiquitous lakes across China's Yangtze Plain (YP) are indispensable freshwater resources sustaining ecosystems and socioeconomics for nearly half a billion people. Our recent survey revealed a widespread net decline in the total YP lake inundation area during 2000–2011 (a cumulative decrease of ∼10%), yet its mechanism remained contentious. Here we uncover the impacts of climate variability and anthropogenic activities including (i) Yangtze flow and sediment alterations by the Three Gorges Dam (TGD) and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 94 publications
1
50
1
Order By: Relevance
“…The water surpluses can be detected in 2010 and 2016, and water deficits can be observed in 2006, 2011 and 2013. The result is inconsistent with the recent findings over the YRB [2,3,42], indicating the flood and drought events in corresponding years. By the way, as shown in the top panel of Figure 2, the differences between the GLDAS and PCR-GLOBWB (SM) can be also seen in 2006 and 2011.…”
Section: Tws Derived From Hydrological Modelscontrasting
confidence: 99%
“…The water surpluses can be detected in 2010 and 2016, and water deficits can be observed in 2006, 2011 and 2013. The result is inconsistent with the recent findings over the YRB [2,3,42], indicating the flood and drought events in corresponding years. By the way, as shown in the top panel of Figure 2, the differences between the GLDAS and PCR-GLOBWB (SM) can be also seen in 2006 and 2011.…”
Section: Tws Derived From Hydrological Modelscontrasting
confidence: 99%
“…These lake effects on streamflow occur in addition to the impacts imposed by the TGD (Wang et al, 2017). These lake effects on streamflow occur in addition to the impacts imposed by the TGD (Wang et al, 2017).…”
Section: Dam Impacts On Summer Streamflowmentioning
confidence: 99%
“…These lakes naturally attenuate the tributary flows, which impact flows to the main stem. These lake effects on streamflow occur in addition to the impacts imposed by the TGD (Wang et al, 2017). (2) The Yangtze River Basin consists of 21 subbasins (see Figure 1), whose runoff forms the main components of inflows at the four downstream hydrological stations.…”
Section: Dam Impacts On Summer Streamflowmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been revealed that the TGD displayed multiple behaviours altering downstream flow characteristics, such as decreasing and increasing discharge during the impoundment and release periods, respectively, and attenuating extreme flood peaks (Dai, Du, Li, Li, & Chen, 2008;Gao et al, 2012;Lai et al, 2014Lai et al, , 2017Mei et al, 2018;Wang, Wang, Lewis, Wu, & Huang, 2017). These variations in flow process due to the TGD were found to induce further hydrological alterations in water levels, droughts, interrelationships between the river and lakes, and even ecosystems of the downstream region (Guo et al, 2012;Li, Xiong, Dong, & Zhang, 2013;Mei, Dai, van Gelder, & Gao, 2015;Wang et al, 2013;Wang, Rhoads, & Wang, 2016;Wang, Sheng, & Wada, 2017;Zhang et al, 2012;Zhang, Ye, et al, 2014). In addition, the TGD was also proved to considerably decline the sediment load of the Yangtze River, resulting in alterations of the downstream river bed and delta (Chen, Wang, Finlayson, Chen, & Yin, 2010;Yang et al, 2006Yang et al, , 2007Zhao et al, 2015).…”
Section: Introductionmentioning
confidence: 99%